Fake Two-Piece Design of Spring and Autumn T-shirts for Elderly Women (Journal of Fiber Bioengineering and Informatics, 2024)
In the context of an ageing population, the research and development of elderly women’s clothing hasbeen widely discussed, and its clothing market has a good prospect. However, research on the designof T-shirts is mainly aimed at young people, and there is still a lack of research on the design of springand autumn T-shirts specifically for elderly women. This paper conducts on-site research to understandthe physical characteristics and clothing needs of elderly women and selects elderly obese women as theresearch object. The spring and autumn T-shirts are designed using a fake two-piece structural stylecombined with imitation woven, knitted fabric, and the rationality of the spring and autumn T-shirtdesign is verified through 3D virtual trial wear.